Root hair length and rhizosheath mass depend on soil porosity, strength and water content in barley genotypes - Haling, Rebecca E; Brown, Lawrie K; Bengough, A. Glyn; Valentine, Tracy A; White, Philip J; Young, Iain M; George, Timothy S (Planta, 2014)
Selecting plants with improved root hair growth is a key strategy for improving phosphorus-uptake efficiency in agriculture. While significant inter- and intra-specific variation is reported for root hair length, it is not known whether these phenotypic differences are exhibited under conditions that are known to affect root hair elongation. This work investigates the effect of soil strength, soil water content (SWC) and soil particle size (SPS) on the root hair length of different root hair genotypes of barley. The root hair and rhizosheath development of five root hair genotypes of barley (Hordeum vulgare L.) was compared in soils with penetrometer resistances ranging from 0.03 to 4.45 MPa (dry bulk densities 1.2–1.7 g cm⁻³). A “short” (SRH) and “long” root hair (LRH) genotype was selected to further investigate whether differentiation of these genotypes was related to SWC or SPS when grown in washed graded sand. In low-strength soil (<1.43 MPa), root hairs of the LRH genotype were on average 25 % longer than that of the SRH genotype. In high-strength soil, root hair length of the LRH genotype was shorter than that in low-strength soil and did not differ from that of the SRH genotype. Root hairs were shorter in wetter soils or soils with smaller particles, and again SRH and LRH did not differ in hair length. Longer root hairs were generally, but not always, associated with larger rhizosheaths, suggesting that mucilage adhesion was also important. The root hair growth of barley was found to be highly responsive to soil properties and this impacted on the expression of phenotypic differences in root hair length. While root hairs are an important trait for phosphorus acquisition in dense soils, the results highlight the importance of selecting multiple and potentially robust root traits to improve resource acquisition in agricultural systems.